US–Russia Confrontation and a New Global Balance. Issue 6 (1st November 2016) - Suslov, Dmitry
Abstract: Although the US–Russia relations are hardly the central axis of contemporary international relations, the systemic confrontation between Moscow and Washington, which began in 2014, will become a decisive factor for the emerging international order. This confrontation was caused by factors much deeper than a mere clash of national interests in Ukraine or Syria. It came as a result of their fundamental disagreement about the basic rules and norms of international relations and a clash of the visions of international order which Moscow and Washington have been promoting since the end of the Cold War. Moreover, this confrontation is a part—and currently the epicentre—of a broader rift between the US and major non-Western centres of power about the nature of a post-hegemonic international order. It put an end to the post-Cold War period of the International System development, and reflects unwillingness of the non-Western power centres to accept the US' global leadership, and US attempts to restore it. Since none of the sides is ready for one-way compromise and all bet on the weakening of the opponent, continuation of the US–Russia confrontation will deepen the split in the Atlantic and Pacific, and intensify the general tendency of global governance bifurcation and emergence of a global divide into two major political and economic communities.